Tax Volunteer Collaborative Contribution in Improving SPT Reporting at KPP Pratama Cicadas - Rulla Mega Nisrina (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to describe the collaborative contribution of the Tax Volunteer program in supporting the improvement of Annual Tax Return (SPT) reporting at KPP Pratama Cicadas. Using a descriptive qualitative approach, data were collected through in-depth interviews and document analysis. The findings indicate that tax volunteers play a significant role in providing assistance during the reporting process, accelerating services, and improving taxpayers' understanding of tax obligations. The collaboration between the Tax Authority, universities, and volunteers is also considered effective in fostering early tax awareness among the public. Despite challenges such as time constraints and limited technical experience among volunteers, the program generally contributes positively to service efficiency and formal compliance. This research recommends strengthening volunteer training, increasing support from university tax centers, and enhancing evaluation systems through logbooks and taxpayer feedback as future development strategies.